Integrative description of a new species of Dugesia (Platyhelminthes, Tricladida, Dugesiidae) from Shennongjia, Central China - Zeng, Zhi-Yu; Wang, Jia; Sluys, Ronald; Guo, Zhi-Peng; Sun, Ting; Huang, Xia-Zi; Li, Shuang-Fei; Wang, An-Tai (Zootaxa, 2024)
A new species of the genus Dugesia (Platyhelminthes, Tricladida, Dugesiidae) from Xiangxi River, Shennongjia Forestry District, Hubei Province, China, is described on the basis of an integrative approach, involving morphology, and molecular systematics. The new species Dugesia saccaria A-T. Wang & Sluys, sp. nov. is characterized by the following features: a dumb-bell-shaped, muscularized hump located just anterior to the knee-shaped bend in the bursal canal; a ventrally displaced ejaculatory duct, which, however, opens terminally through the dorsal portion of the blunt tip of the penis papilla; a ventrally located seminal vesicle, giving rise to a vertically running duct that eventually curves downwards to communicate with the ejaculatory duct via a small diaphragm; oviducts opening asymmetrically into the dorsal portion of the common atrium and at the knee-shaped part of the bursal canal. The phylogenetic position of the new species was determined using four molecular markers (18S rDNA; ITS-1; 28S rDNA; COI), which suggested that it groups with other species of Dugesia from the Australasian and Oriental biogeographical regions.